2017
DOI: 10.1002/jbt.21898
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of capsaicin inhibition of aldose reductase activity

Abstract: Aldose reductase (AR) inhibitors play a vital importance as a potential therapeutic and preventive medicine when it comes to hyperglycemia associated diabetic complications. Additionally, capsaicin is used as a food additive and a drug in a number of diverse clinical trials. The aim of this study is to determine the in vitro inhibition behavior of capsaicin on AR enzyme activity, which was obtained from different rat tissues (heart, kidney, liver, and brain). We showed that AR was inhibited by capsaicin in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Many studies showed that AR is a significant pharmacological target and its inhibition can have a role in the treatment of diabetic complications . Therefore, there is a need for effective and new ARIs.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies showed that AR is a significant pharmacological target and its inhibition can have a role in the treatment of diabetic complications . Therefore, there is a need for effective and new ARIs.…”
Section: Resultsmentioning
confidence: 99%
“…In order to calculate Ki values of triazole derivatives showing the inhibitory effect on aldose reductase enzyme, activity values were determined with 3 different inhibitor concentrations against 5 different substrate concentrations. Lineweaver-Burk plots of each compound were drawn from the activity values obtained and Ki values and inhibition types were determined from graphics equations (Alim et al 2017;Taslimi et al 2018).…”
Section: Aldose Reductase Activity Assay and Inhibition Studiesmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a global metabolic disease accompanied by hyperglycemia and glucose metabolic dysfunction, and it has been estimated that nearly 642 million individuals will develop diabetes by 2040. 1 Aldose reductase (AR, AKR1B1; EC 1.1.1.21) is a polyol pathway enzyme 2 whose overexpression in DM leads to diabetic consequences such as neuropathy, 3 retinopathy, 4 cataracts, 5 nephropathy, 6 and cardiovascular diseases. 7 Therefore, inhibiting AR is among the most important drug targets (Figure 1).…”
Section: Introductionmentioning
confidence: 99%